Deteksi Diarrhoegenic E. coli pada Sampel Feses Penderita Diare di Puskesmas Batulicin dan Pagatan Kabupaten Tanah Bumbu dengan Metode Polymerase Chain Reaction (PCR) - Ika Setianingsih; Dicky Andiarsa; Erli Hariyati (Biomedika, 2019)
Diarrhoegenic E. coli (DEC) is a group of pathogenic E. coli strains known to be one of the causes of diarrheal disease. Diarrhea cases are still quite high in developing countries like Indonesia. Tanah Bumbu Regency, especially Batulicin and Pagatan, have a fluctuating rate of diarrhea. This study aims to detect DEC in diarrheal patients in the work area of ​​Batulicin and Pagatan Health Centers using the PCR examination method. Cross Sectional research design with a total sample of 15 respondents collected for 3 months (August - October 2019). Stool samples were examined using the PCR method to detect the presence of DEC strains namely EAEC, ETEC, and EPEC and EHEC. Three out of fifteen (20%) samples were known to be positive for Diarrhoegenic E. coli (DEC). ETEC strains were found in 2 (0,13%) sample, each from the Batulicin Health Center and the Pagatan Health Center, while EPEC and EAEC strains were found in the same 1 (0,07%) sample from the Pagatan Health Center. EHEC strain was not detected in all samples. Diarrhogenic E. coli strains found in this study are EAEC, ETEC, and EPEC. However, it cannot be ascertained yet that the three strains are the cause of the diarrheal disease, it needs to be further to do comprehensive research. The community should be able to increase awareness of the importance of clean and healthy behavior, especially food and beverages consumption, so it can reduce the number of diarrhea cases.